Effectiveness of a multidrug therapy consisting of Ivermectin, Azithromycin, Montelukast, and Acetylsalicylic acid to prevent hospitalization and death among ambulatory COVID-19 cases in Tlaxcala, Mexico. (April 2021) - Lima-Morales, René; Méndez-Hernández, Pablo; Flores, Yvonne N.; Osorno-Romero, Patricia; Sancho-Hernández, Christian Ronal; Cuecuecha-Rugerio, Elizabeth; Nava-Zamora, Adrián; Hernández-Galdamez, Diego Rolando; Romo-Dueñas, Daniela Karola; Salmerón, Jorge
Highlights: TNR4 is a multidrug therapy (Ivermectin, Azithromycin, Montelukast, and ASA) for COVID-19 cases. TNR4 increased the likelihood of recovery 3.4 times in ambulatory COVID-19 cases. The multidrug therapy TNR4 reduced the risk of hospitalization by 75%. The multidrug therapy TNR4 reduced the risk of death by 81%. Abstract: Objective: There is an urgent need for effective treatments to prevent or attenuate lung and systemic inflammation, endotheliitis, and thrombosis related to COVID-19. This study aimed to assess the effectiveness of a multidrug-therapy consisting of Ivermectin, Azithromycin, Montelukast, and Acetylsalicylic acid ("TNR4" therapy) to prevent hospitalization and death among ambulatory COVID-19 cases in Tlaxcala, Mexico. Design and methods: A comparative effectiveness study was performed among 768 confirmed SARS-CoV-2 cases aged 18–80 years, who received ambulatory care at the Ministry of Health of Tlaxcala. A total of 481 cases received the TNR4 therapy, while 287 received another treatment (comparison group). All participants received home visits and/or phone calls for clinical evaluation during the 14 days after enrollment. Results: Nearly 85% of cases who received the TNR4 recovered within 14 days compared to 59% in the comparison group. The likelihood of recovery within 14 days was 3.4 times greater among the TNR4 group than in the comparison group. Patients treated with TNR4 had a 75% and 81% lower risk of being hospitalized or death, respectively, than the comparison group. Conclusions: TNR4 therapy improved recovery and prevented the risk of hospitalization and death among ambulatory COVID-19 cases.